Outcomes of a multifaceted intervention to improve maternal satisfaction with care in secondary hospitals in Nigeria. Issue 1 (31st December 2020) - Okonofua, Friday E.; Ntoimo, Lorretta Favour C.; Ekezue, Bola F.; Ohenhen, Victor; Agholor, Kingsley; Igboin, Brian; Maduako, Kenneth; Imongan, Wilson; Gidago, Yagana; Galadanci, Hadiza; Ogu, Rosemary
ABSTRACT: Background : Data in Nigeria suggests a high level of dissatisfaction among women attending maternity care in health facilities due to long wait times, disrespectful care, and poor attention by healthcare personnel. Objective : To examine the effectiveness of a multifaceted intervention in improving self-reported indicators of maternal healthcare satisfaction by women who use referral facilities in two regions of Nigeria. Method : The design was quasi-experimental and consisted of two intervention facilities and two control facilities. The interventions included strategic planning, staff re-training, a computerized appointment system, health education/feedback, maternal death reviews and surveillance, and advocacy. A random sample of 2262 women was selected (1205 in the intervention sites and 1057 in the two control sites) to respond to a 24-item questionnaire on service satisfaction as they exited the health facilities. Adjusted Poisson and binary regression analyses were used to assess and compare proportions of reported satisfaction by women between the intervention and control sites. Results : Women in the intervention sites were 54% more likely than those in control sites to report overall satisfaction with services. They were significantly less likely to report inadequate security arrangements in accessing the health facilities (p < .1); and three times more likely to agree that health workers were extremely thorough and careful in attending to them (p < .1). Conclusion : The interventions had positive effects on improving women's satisfaction with care. The findings from this study have implications for the design and implementation of interventions that address women's concerns relating to the provision of care and consequently improve service utilization.